Pemanfaatan SATUDIK (Sajian Mutu Pendidikan) Sebagai Alat Monitoring Mutu Pendidikan oleh Pengawas SMP di Kabupaten Luwu - Nurhidayah Nurhidayah; Aris Munandar; Ansar Ansar (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: This study aims to analyse the utilization of SATUDIK as a tool for monitoring educational quality by junior high school supervisors in Luwu Regency. The focus of the study includes the implementation of the Internal Quality Assurance System (SPMI) cycle, the level of SATUDIK utilization, and the supporting and inhibiting factors affecting its use in educational quality supervision. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving junior high school supervisors, principals, and related educational stakeholders. Data analysis applied the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing/verification. Data validity was strengthened through source triangulation, technique triangulation, and member checking. The findings indicate that SATUDIK has contributed significantly to strengthening data-based quality monitoring, particularly in the stages of quality mapping and evaluation. However, its utilization has not been evenly implemented and has not been fully integrated into the school planning and quality improvement cycle. The main supporting factors include policy support, availability of integrated data, training programs, and supervisors’ digital competencies. Meanwhile, the inhibiting factors consist of low data literacy, inconsistent data quality, limited infrastructure, and a school work culture that is not yet fully data-driven. This study confirms that the success of SATUDIK is determined not only by the availability of digital platforms but also by human resource capacity, quality leadership, and an evidence-based decision-making culture. Keywords: SATUDIK, school supervisors, quality monitoring, Internal Quality Assurance System (SPMI), educational data. Abstrak: Penelitian ini bertujuan menganalisis pemanfaatan SATUDIK sebagai alat monitoring mutu pendidikan oleh pengawas SMP di Kabupaten Luwu. Fokus penelitian mencakup pelaksanaan siklus Sistem Penjaminan Mutu Internal, tingkat pemanfaatan SATUDIK, serta faktor pendukung dan penghambat penggunaannya dalam pengawasan mutu pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan studi dokumentasi terhadap pengawas SMP, kepala sekolah, serta pemangku kepentingan pendidikan terkait. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan/verifikasi. Keabsahan data diperkuat melalui triangulasi sumber, triangulasi teknik, dan member check. Hasil penelitian menunjukkan bahwa SATUDIK telah berkontribusi dalam memperkuat monitoring mutu berbasis data, terutama pada tahap pemetaan dan evaluasi mutu. Namun, pemanfaatannya belum merata dan belum sepenuhnya terintegrasi dalam siklus perencanaan dan peningkatan mutu sekolah. Faktor pendukung utama meliputi dukungan kebijakan, ketersediaan data terintegrasi, pelatihan, serta kompetensi digital pengawas. Sementara itu, faktor penghambat mencakup rendahnya literasi data, kualitas data yang belum konsisten, keterbatasan infrastruktur, dan budaya kerja sekolah yang belum sepenuhnya berbasis data. Penelitian ini menegaskan bahwa keberhasilan SATUDIK tidak hanya ditentukan oleh ketersediaan platform digital, tetapi juga oleh kapasitas sumber daya manusia, kepemimpinan mutu, dan budaya pengambilan keputusan berbasis bukti. Kata kunci: SATUDIK, pengawas sekolah, monitoring mutu, SPMI, data pendidikan